2010
DOI: 10.1177/1082013209353240
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension and Mechanism of Aggregation of Apple Juice Particles

Abstract: Turbidity of freshly squeezed apple juice is produced by a polydisperse suspension of particles coming from the cellular tissue. After precipitation of coarse particles by gravity, only fine-colloidal particles remain in suspension. Aggregation of colloidal particles leads to the formation of fractal structures. The fractal dimension is a measure of the internal density of these aggregates and depends on their mechanism of aggregation. Digitized images of primary particles and aggregates of depectinized, diafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Twenty different SEM images of SG aggregates were subjected to the FERImage program which calculates fractal dimension ( D f ) by means of a variogram and a Fourier power spectrum (Bianchi & Bonetto, ). The methodology described was previously used with aggregates of apple juice (Benítez et al ., ) and beer (Benítez et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Twenty different SEM images of SG aggregates were subjected to the FERImage program which calculates fractal dimension ( D f ) by means of a variogram and a Fourier power spectrum (Bianchi & Bonetto, ). The methodology described was previously used with aggregates of apple juice (Benítez et al ., ) and beer (Benítez et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…[4,6] Unlike citrus juice, in apple juice suspended cloud particles should be removed to make a clear juice by different methods like enzyme clarification. [29,41] It was reported that the aggregation of cloud particles took place immediately after pectin de-esterification by adding pectolytic enzymes to the turbid apple juice. [29] It was also mentioned that a de-esterified colloid particle diffuses until it meets another particle to create a 'fractile cluster' or an 'island structure' or joins an existing island to extend it.…”
Section: Effect Of Cut On Lightness Of the Colourmentioning
confidence: 99%
“…[29,41] It was reported that the aggregation of cloud particles took place immediately after pectin de-esterification by adding pectolytic enzymes to the turbid apple juice. [29] It was also mentioned that a de-esterified colloid particle diffuses until it meets another particle to create a 'fractile cluster' or an 'island structure' or joins an existing island to extend it. This island structure is in agreement with self-similarity properties of a fractal structure.…”
Section: Effect Of Cut On Lightness Of the Colourmentioning
confidence: 99%
See 2 more Smart Citations